2004
DOI: 10.1039/b405141f
|View full text |Cite
|
Sign up to set email alerts
|

Radical addition of nitrones to acrylates mediated by SmI2: asymmetric synthesis of γ-amino acids employing carbohydrate-based chiral auxiliaries

Abstract: Alkyl nitrones possessing N-substituted sugars as chiral auxiliaries were found to effectively undergo an SmI(2)-mediated radical addition to n-butyl acrylate affording gamma-amino acid derivatives with high diastereomeric control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 11 publications
1
18
0
2
Order By: Relevance
“…Chiral auxiliaries have been used, either as substituents at the nitrone nitrogen atom or at the unsaturated ester or amide, to achieve enantioselectivity (Scheme ) 16. 17 The latter approach afforded up to 90:10 d.r. (for example, in the synthesis of γ‐hydroxyaminoester 33 ),16b while the former one gave moderate to very good enantioselectivity for N ‐benzyl‐type substituents16a and excellent enantioselectivity for N ‐glycosylnitrones, such as 34 17.…”
Section: Methodsmentioning
confidence: 99%
“…Chiral auxiliaries have been used, either as substituents at the nitrone nitrogen atom or at the unsaturated ester or amide, to achieve enantioselectivity (Scheme ) 16. 17 The latter approach afforded up to 90:10 d.r. (for example, in the synthesis of γ‐hydroxyaminoester 33 ),16b while the former one gave moderate to very good enantioselectivity for N ‐benzyl‐type substituents16a and excellent enantioselectivity for N ‐glycosylnitrones, such as 34 17.…”
Section: Methodsmentioning
confidence: 99%
“…Catalytic hydrogenation of diastereoisomerically pure anti-253 followed by N-protection with di(tert-butyl)dicarbonate (Boc) 2 O produced 255 in 82% yield, which is a key intermediate 109 in the synthesis of (S)-vigabatrin 2 (Scheme 57). 110 Recently, Skrydstrup et al 111 reported that the addition of chiral N-D D-mannose substituted nitrones 256a-d to n-butyl acrylate in the presence of SmI 2 to afford the c-amino acid derivatives 257a-d in moderate yield and 95:5 diastereoisomeric ratio, with predominance of diastereoisomer of (R)-configuration at the newly created stereogenic center (Scheme 58).…”
Section: C-substituted C-amino Acidsmentioning
confidence: 97%
“…111 Derivatives 257a-d and 259a-c are useful intermediates for the synthesis of c-substituted c-amino acids.…”
Section: C-substituted C-amino Acidsmentioning
confidence: 99%
“…with the major (R) diastereoisomer (Scheme 13.9) [19]. The same reaction when applied to N-D-ribose substituted nitrones (34) afforded the corresponding g-substituted-a-amino acid precursor (35) with opposite (S) configuration, indicating the choice of sugar nitrone as a tool for obtaining either (R) or (S) enantiomers.…”
Section: G-amino Acidsmentioning
confidence: 98%